Ectopic bronchogenic cyst of the gastric cardia considered to be a gastrointestinal stromal tumor before surgery: a case report - Xiao, Jianchun (BMC Surg, 2020)
BACKGROUND: We herein report a rare case of an ectopic bronchogenic cyst of the gastric cardia. The initial diagnosis was a gastrointestinal stromal tumor (GIST); however, postoperative pathologic examination confirmed that it was a bronchogenic cyst. CASE PRESENTATION: A 62-year-old woman visited our hospital for abdominal pain. The diagnosis prior to surgery was a GIST. Computed tomography imaging showed that the mass was located in the gastric cardia on the side of the lesser curvature. During the surgical exploration, it was noted that the tactility of the mass was not consistent with a GIST. Thus, we decided to perform local resection of the mass and part of the gastric wall without wedge resection. The pathological examination revealed a bronchogenic cyst. CONCLUSIONS: This case suggests that a bronchogenic cyst should be considered as a differential diagnosis of a GIST. It is also a unusual but necessary situation should be considered when explaining the etiology of a bronchogenic cyst.